Production of Modified Cassava Flour (MOCAF) - Bahrun, Mohd Shakir (2013)
Nowadays the Malaysia population expected to be increased as well as the consumption of food required especially on the agriculture sector. This result also effect the amount of wheat imported to Malaysia which is following the same statistics. Due to this matter, Modified Cassava Flour (MOCAF) has been developed to overcome the problem. By having the MOCAF which derived from local crops cassava, it can become one of the alternatives for substituting the wheat consumption in this country. Malaysian MOCAF Sdn Bhd is the first company in Malaysia that producing MOCAF. Due to the reason of competing in wheat flour based food industry, the company is producing special flour that have a similar wheat flour characteristic with a low price to the related industries in order to reduce their raw material cost and increasing their profitability. Malaysian MOCAF Sdn Bhd is a flour production company that targeting the wheat based food which is baked goods, biscuits and noodles industries as the starting business. This company is located at Sipitang Sabah and only targeting the local market. Even though the market is only focusing in Malaysia, the value of the market is quite high which reach 14.95 Million only for baked goods industry. This market value might be increase by the time MOCAF being commonly used in Malaysia industry. The competitive analysis shows that the Malaysian MOCAF Sdn Bhd will be survive in the market even though there are several flour mill company already established in Malaysia. This is due to the high demand in the related industries and the availabilities of customer with high annual income. Malaysian MOCAF Sdn Bhd estimated to finish the start-up period at the beginning of January 2015 and the first production will come on March 2015. The Company is a partnership associated with 3 members as shareholders and a total of 25 employees for the beginning operation. The company sell the products directly to the customers without having an intermediary this due to the quality service that being implemented by the company which to maintain the quality of the product as well as the reliable price received by the customer. The potential and experienced management team will lead the company to become more competitive in the industry. The Flexible manufacturing strategies choosewould help the company survive if there are any changes in the market and keep thegood satisfaction to the customer. Malaysian MOCAF Sdn Bhd will require investment RM 4 Million to start operating the business. RM 1 Million will be provided by the shareholders while the remaining RM 3 Million was expect to get from Bank Loan. The payback period of the investment estimate to be after four and a half year. The starting sales production is 13250 units per month and will increase to 20384 units per month at the end of five years. The profit of the first year estimate to be RM 170,755.00 and drastically increases to RM 1,414,504.00 at the end of year five. In order to reduce the external funding, the loan payment of RM 300,000.00 will start at the first year. The Balanced Sheet shows that the company will have a total asset of 7 Million at the end of year five compare to the 4 Million at the beginning of start-up. All the details are explained in the Financial Analysis. In conclusion, the profitability of Malaysian MOCAF Sdn Bhd will be substantial and will generate high shareholders value. It can become the world’s major supplier of MOCAF for industry purposes in the near future based on the superior of qualities of the product at extremely competitive price and generating attractive profit margin for the customer.